Fabrication & Tribological Study of Copper Based Sintered Composites - Somani, Nalin (My University, 2016)
Metal matrix composite using copper as a base material is gaining huge attention in multiple applications because of their good electrical, thermal and mechanical properties. A composite of Cu-SiC with different combinations were fabricated by using powder metallurgy technique. Compositions ranging from 100% copper to 80% copper-20%SiC with nickel and graphite as a binder and wetting agent were sintered and fabricated. Pin-On-Disc machine was used to examine the tribological properties of the composites under the different loads and sliding speed. The addition of the SiC as a reinforcement in Cu-SiC composite increases the wear resistance capacity and reduces the coefficient of friction. ANOVA was used to understand the significance of process variables which were affecting wear rate and the coefficient of friction. Normal load and the sliding distance are found to be most significant process parameters which were affecting the wear rate as well as coefficient of friction. Empirical statistical models have been developed for predicting the value of wear rate and coefficient of friction by using the regression equations. Obtained results were compared with the experimental results and they were found in good agreement with experiments. Scanning electron microscope (SEM) and Optical microscopes were used to interpret the morphology of worn surface and to comprehend the wear mechanism. Keywords:
Keywords: Powder metallurgy; Wear Rate; Coefficient of friction; Taguchi method; ANOVA